ADOLESCENT AGGRESSION IN CHORNOBYL AREA: SELF-CONTROL, IDENTITY AND MORAL DEVELOPMENT - Volodymyr Khomyk (Психологічні перспективи, 2014)
Self-reported aggression by adolescents from the Chornobyl area revealed that epistemological course in their constitution of everyday reality finds expression in an Imperial way of knowing and awareness. Control over own needs, desires and priorities as the very essence of self in violent situations is related to a lack of protective frame in consciousness of adolescents. Chornobyl adolescents create something which they avoid and fear or do not make the ordinary meaning of human experience and differentiation from others come before integration and wholeness in their awareness. To young men who are at the delayed stage of consciousness development, aggression most frequently correlated with the experience of pleasant toughness instead the negativistic/conformist pair of metamotivational states, implying that rules are not experienced by individuals as shared reality that are given shape and order. Rather, it was perceived as amorphous, unstable and inherently fluctuating set of moral standards. For the Interpersonal self, the other-oriented mastery state much better corresponds to self-control in fight situations than other metamotivational states do.